Analisa Kadar Kalori, Kadar Air, dan Masa Simpan dengan Menggunakan Teknologi Pengiris Guna Produktifitas Produk Keripik Singkong - Handajani, Sri; Yasin, Ach; Basukiwardojo, Maria Monica Sianita; Kusumawati, Nita; Kurniawan, Muhammad Ridho Hafid; Rahayu, Nunik Tri; Estiningtyas, Indri Wasa (Abimanyu : Jornal of Community Engagement, 2024)
Cassava can be processed into chips, which have a special appeal with their distinctive flavour and crunchy texture. Cassava chip production creates profits for cassava farmers and is a major industry in some regions. Improving product quality involves various control measures, including handling and packaging of the final product. The frying and draining process is an important factor in extending the shelf life and inhibiting oxidation of a product. The purpose of this study was to determine the effect of the use of appropriate technology (TTG) draining machines on the nutrition and shelf life of cassava chips products. The results showed that the total fat, saturated fat, protein and carbohydrate content of cassava chips products as a result of TTG were 4.91%; 2.26%; 3.11%; 81.01%, respectively. The shelf life of the chips was 5.25 months (157.5 or 158 days). The results of the organoleptic test of cassava chips in terms of colour, aroma, texture and overall liking level received a positive response from the community, both teenagers and adults. The aspects of aroma, taste, texture and colour as well as the overall level of liking with a percentage level of 80% (seblak daun jeruk), 58% (fried chicken), 61% (rendang), and 56% (grilled chicken).